2022
DOI: 10.3389/fonc.2022.840855
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effects of Repetitive Transcranial Magnetic Stimulation in Patients With Advanced Non-Small-Cell Lung Cancer: A Randomized, Sham-Controlled, Pilot Study

Abstract: ObjectiveCurrent pharmacological intervention for the cancer-related pain is still limited. The aim of this study was to explore whether repetitive transcranial magnetic stimulation (rTMS) could be an effective adjuvant therapy to reduce pain in patients with advanced non-small cell lung cancer (NSCLC).MethodsThis was a randomized, sham–controlled study. A total of 41 advanced NSCLC patients with uncontrolled pain (score≥4 on pain intensity assessed with an 11-point numeric rating scale) were randomized to rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Due to the loss of motor function after stroke, this excitatory stimulation has important implications for relearning during motor rehabilitation ( 13 ). In recent years, rTMS has been widely used to treat neuropsychiatric disorders such as depression, epilepsy, pain, and Parkinson's disease ( 14 17 ). However, despite the therapeutic potential, many participants reported adverse effects of rTMS, including headache, muscle twitching, and residual hypersensitivity ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the loss of motor function after stroke, this excitatory stimulation has important implications for relearning during motor rehabilitation ( 13 ). In recent years, rTMS has been widely used to treat neuropsychiatric disorders such as depression, epilepsy, pain, and Parkinson's disease ( 14 17 ). However, despite the therapeutic potential, many participants reported adverse effects of rTMS, including headache, muscle twitching, and residual hypersensitivity ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…All studies were double-blind, parallel, sham-controlled RCTs with no baseline demographic diferences. Te included studies enrolled a total of 269 patients with pain secondary to malignancy including hepatocellular carcinoma (HCC) [33], breast cancer [35], nonsmall cell lung cancer (NSCLC) [36], or mixed-origin cancers [34]. Most of the studies reported chronic (at least 2 months) and uncontrolled pain secondary to the cancer itself or to cancer-related treatments, including surgery, chemotherapy, or radiotherapy [33,35,36].…”
Section: Study Characteristics and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Te baseline pain score was rated with the BPI at 1.24 to 1.45 and reevaluated twice during CES treatment of 1 hour stimulation per day for 2 weeks. In Tang et al's study, 39 patients with NSCLC had intractable pain even with the use of morphine or oxycodone [36]. Te patients received rTMS for 3 weeks targeting the left dorsolateral prefrontal cortex (DLPFC) with 1500 pulses of 10 Hz stimulation for 3 weeks.…”
Section: Study Characteristics and Risk Of Bias Assessmentmentioning
confidence: 99%
See 2 more Smart Citations